General Synod of the Church of Ireland: May 2016. (20th December 2016) - Davey, Michael; Turner, Kate
Abstract : This year's General Synod, the second meeting of the triennium, was held in Dún Laoghaire, to the south of Dublin. It was a hotel conference venue, albeit one new to the Synod meeting. The Synod passed Bills relating to the areas of episcopal election and part-time ministry, as well as the ongoing areas of charity legislation and pensions. A Bill relating to diocesan boundaries was withdrawn.